Exploring the public-private sector wage gap in European countries - Louis N. Christofides; Maria Michael (IZA Journal of European Labor Studies, 2013)
We estimate the public-private sector pay gap for 27 European countries, using the 2008 EU SILC. The coefficients of conditional (on personal and job characteristics) public sector controls give a first impression on wage differences, while decompositions into explained and unexplained components (also accounting for selectivity) allow for a more complete analysis, which helps to identify possible causes of the gap. Regional patterns exist. Separate subsample decompositions based on age, education, gender and occupation, provide interesting insight regarding the pay structure of each country. Quantile decomposition analyses show that the public-private pay gap is, generally, negatively related to income quantiles.
Keywords: J31; J45; J48; 330; Pay gap; Public; Private sector; Decompositions; Quantiles